PTH-091 Incidental Diagnosis of Inflammatory Bowel Disease Through The Bowel Cancer Screening Programme: A 7 Year Experience. (17th August 2016) - Nosegbe, U; Scott, J; Butcher, R; Abbasi, A; Prudham, R; George, R; Limdi, JK
Abstract : Introduction: The UK Bowel Cancer Screening Programme (BCSP) launched in 2006, currently screens individuals aged 60–74 years through a Faecal Occult Blood test (FOBt). If positive patients are invited for colonoscopy. We reported in 2012 the first ever experience of incidental diagnosis of IBD through a screening cohort and now present a 7 year experience. Methods: We conducted a retrospective assessment of BCSP outcomes at our centre between April 2008 (launch) and December 2015. Assessment included the number of patients invited for screening, number successfully screened (inclusive of "normal" and "abnormal" FOBt) and the number of index colonoscopies. In those with confirmed IBD diagnosis, clinical outcomes, symptoms at diagnosis, disease distribution and behaviour and treatments undertaken were recorded through patient record and case note reviews. Results: Of 358, 716 invited individuals 180, 075 were adequately screened (uptake 50.2%) with FOBt positivity of 1.83%. Of 3598 index colonoscopies undertaken, an incidental diagnosis of IBD was made in 37 (12 female) patients. Ulcerative Colitis (UC) was diagnosed in in 22 (59.4%) patients and Crohn's (CD) in 10 (27.0%). A further 5 (13.5%) patients were diagnosed with IBD-type unclassified (IBDU) of which 2 were reclassified as UC through follow up. In those diagnosed with UC initially 9 (41.0%) had proctitis, 8 (36.4%) left sided disease and 5 (22.7%) had extensive disease. The majority of CD patients (80%) had an isolated colonic distribution and behaviour was non-stricturing and non-penetrating (70%) or stricturing (30%). Follow up data was available for 25 (67.6%) patients over a median of 40.5 months (range 3–87) of which 14 patients were asymptomatic at diagnosis. Eleven (78.6%) became symptomatic and 2 (8.3%) demonstrated phenotypic progression during follow up. Treatment included 5 ASA (23), steroids (14), Immunomodulation (Azathioprine – 7: Methotrexate – 1) and Anti-TNF (Infliximab -2; Adalimumab – 1). Median time to immunomodulation was 29.0 months and to anti-TNF treatment was 28.0 months. Five patients died: 3 from unrelated causes, 1 from an unknown cause and 1 seven days after subtotal colectomy (undertaken 54 months after diagnosis with symptomatic IBDU). Conclusion: An incidental diagnosis of IBD at screening is not uncommon, with an incidence of 1.0% in our cohort . A proportion of patients demonstrate significant disease progression requiring immunomodulation, biologic therapy or surgery. IBD detection from screening provides a unique model to study early disease in 'elderly' (and potentially asymptomatic) patients. Disclosure of Interest: None Declared